Perspectives of Indigenous medical students on a postgraduate Indigenous admissions pathway - Black, Kristin A; Schroeder, Brittany; Felske-Durksen, Cassandra; Rich, Rebecca (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Objective: The objective of this study is to assess the perceptions of Indigenous medical students on postgraduate admissions through an Indigenous admissions pathway (IAP), and to determine what factors may influence Indigenous medical students’ choice of residency training program.Methods: We distributed a survey to self-identified Indigenous students at settler Canadian medical schools. The survey questioned the students’ acceptability of an IAP, and what factors would influence application through an IAP. Analysis included descriptive statistics and thematic analysis of open-ended questions.Results: Thirty-six participants responded to the survey. Location and proximity to family or support system were the most important factors in choosing a residency program. Participants identified mentorship from Indigenous physicians and community involvement as being important features of a residency program that has an IAP. Eighty-one percent of participants felt the availability of an IAP would influence their choice of residency program. Fear of judgement or stigma, concern about entrance requirements, and program logistics were identified as barriers to applying to residency through an IAP. All participants believed that an IAP would have a positive influence on the healthcare system more broadly.Conclusions: An IAP appears to be an acceptable residency application format to Indigenous students but cannot exist in isolation. It is important for programs to consider the needs and safety of Indigenous trainees within residency programs.